1992
DOI: 10.1152/ajpregu.1992.263.2.r279
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide inhibits amiloride-sensitive sodium uptake in rat brain

Abstract: Both atrial natriuretic peptide (ANP) and its receptors are present in the central nervous system, but effects of ANP on brain are unclear. In the present study, we evaluated both the effects of ANP on sodium uptake, and a possible effector mechanism, the putative intracellular second messenger guanosine 3',5'-cyclic monophosphate (cGMP), in rat brain synaptosomes. In the presence of ANP (10(-7) M), the basal level of sodium uptake in synaptosomes was reduced (n = 6) from the control value of 1.90 +/- 0.06 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…ANP can early regulate pHi through NHE-1 [12,13,34]. In fact, pharmacological concentrations of the hormone inhibit NHE-1 by a mechanism that includes increased intracellular levels of cGMP, while physiological concentrations can stimulate NHE-1 through the diacylglycerol production or cAMP decrease [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANP can early regulate pHi through NHE-1 [12,13,34]. In fact, pharmacological concentrations of the hormone inhibit NHE-1 by a mechanism that includes increased intracellular levels of cGMP, while physiological concentrations can stimulate NHE-1 through the diacylglycerol production or cAMP decrease [13].…”
Section: Discussionmentioning
confidence: 99%
“…Among different biological effects, in hepatoblastoma (HepG2) cells, ANP inhibits cell proliferation through the selective upregulation of the expression of the NPR-C receptors associated with decreased intracellular concentrations of cAMP [11]. Furthermore, ANP can inhibit or stimulate Na + /H + exchanger isoform 1 (NHE-1) depending on cell type [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Amiloride-sensitive sodium uptake. Sodium uptake was determined in synaptosomes with or without amiloride (1 mM) (25). An aliquot of synaptosomes was incubated with four volumes ofpreequilibrium media ([in mM] KCl, 150; MgCl2, 1; Hepes-Tris, 5; pH 7.40) for 10 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…More than fifteen years ago, it has been reported that ANP is able to modify the intracellular pH by inhibiting or stimulating the NHE-1, depending on the cell type [55, 56]. In the 2005, Baldini and collaborators demonstrated that in HepG2 hepatoblastoma cells, ANP induced intracellular acidification by decreasing NHE-1 expression and activity [57].…”
Section: Innovative Targets For Antitumor Activity Of Anpmentioning
confidence: 99%